Kyrles Disease: A Rare Skin Manifestation of Systemic Diseases - Sahoo, Aswini Kumar; Rauta, Sudhasmita (Journal of Medicine, 2014)
A 39-year-old man of diabetic nephropathy presented with pruritic papulo-nodular brown lesions in both arms and legs on extensor surface characterized by central keratin plugs. Lesions were non-tender and numerous, crusted lesions which histologically were perforating disorders, showing features of Kyrle disease. The blood sugar of the patient was kept under control & hemodialysis was started. Dermatological lesions were treated by Isotretinoin, vitamin A, Tretinoin cream and oral antihistamines. DOI: http://dx.doi.org/10.3329/jom.v15i2.20689 J MEDICINE 2014; 15 : 144-145